KEDUDUKAN PENERIMA FIDUSIA DALAM PEMBEBANAN JAMINAN FIDUSIA YANG DIBUAT DENGAN AKTA DIBAWAH TANGAN - Ni Made Trisna Dewi (Fakultas Hukum Universitas Dwijendra, 2021)
Abstract In the practice of banking, material guarantees are preferred by banks, one type of material guarantee known in positive law is fiduciary guarantees, as guarantee institutions for movable objects. In banking practice, fiduciary guarantees cannot be separated from credit problems. As a material guarantee in banking practice, fiduciary guarantees are very popular and popular because they provide benefits for people who need funding/credit for small and medium-sized communities. The problems that will be discussed in this study are: 1) Does the imposition of a fiduciary guarantee with an underhand deed have binding power? and 2) What is the position of the recipient of the fiduciary guarantee in the case that the imposition of the fiduciary guarantee is made with a private deed?The research method used in this paper is an empirical legal research method, namely legal research based on the results of field research on a predetermined research object. Then it is associated with statutory provisions based on a normative study by examining a legal product based on theories and legal principles directly, in order to obtain material truth in order to obtain improvements in the preparation of this research.The results of this study are: 1) The imposition of an authentic deed guarantee, namely a notary deed. The imposition of a fiduciary guarantee which is only made with a deed under the hand does not have binding power, because it contains a cause that is prohibited or not in accordance with the provisions of the law, 2) The position of the recipient of the fiduciary guarantee in the case of the imposition of a fiduciary guarantee made in a deed under the same hand position with an authentic deed, as long as there are no problems or defaults.